Anger in Negotiations: A Review of Causes, Effects, and Unanswered Questions. (14th July 2017) - Hunsaker, David A.
Abstract: This article reviews the literature on the emotion of anger in the negotiation context. I discuss the known antecedents of anger in negotiation, as well as its positive and negative inter‐ and intrapersonal effects. I pay particular attention to the apparent disagreements within the literature concerning the benefits and drawbacks of using anger to gain advantage in negotiations and employ Attribution Theory as a unifying mechanism to help explain these diverse findings. I call attention to the weaknesses evident in current research questions and methodologies and end with suggestions for future research in this important area.